Adiksi Sosial Media: Peran Kecenderungan Fear of Missing Out dan Regulasi Diri - Agatha Prajna Devi Ardhini; Marselinus Sampe Tondok (Universitas Negeri Makassar, 2023)
Social media addiction has become an increasingly relevant mental health issue along with the intensification of social media use. This study aims to investigate the role of fear of missing out (FOMO) tendencies and self-regulation in the context of social media addiction. The study involved 253 participants aged 18-25, active social media users residing in East Java. Data was collected using scales measuring social media addiction, FOMO, and self-regulation. Data analysis to test hypotheses was conducted through multiple regression using SPSS 25.0 for Windows. The results of the analysis indicate a combined influence of FOMO tendencies and self-regulation on social media addiction, amounting to 58% (F = 117.308, R2 = 0.580, p < 0.001). Partially, FOMO tendencies have a positive role, contributing to a 48% increase in social media addiction (β = 0.667, R2 = 0.480, p < 0.05). Meanwhile, self-regulation does not significantly explain social media addiction (β = 0.070, R2 = 0.100, p > 0.05). The implications of this research emphasize the importance of recognizing the impact of FOMO tendencies on social media addiction in managing user behavior and serving as a basis for developing more effective intervention strategies to reduce social media addiction.